Diplomasi Publik Indonesia terhadap Vanuatu Dalam Upaya Membendung Gerakan Separatisme Papua - Ahmad Sabir (Jurnal Hubungan Internasional, 2018)
Abstract This research explains Indonesia diplomacy to Vanuatu in the context of the Indonesian government's efforts to resolve separatism issue in Papua. The analysis conducted on this thesis uses the theory of Public Diplomacy by Leonard, Stead and Smewing (2002). The result of this research is the failure of Indonesian public diplomacy to shape Vanuatu political stance on Papua issue caused by the failure in optimizing the strategies of Indonesian public diplomacy. Vanuatu yet staunchly supports Papua separatist movement. There are at least three reasons that are closely related to the weakness of Indonesian public diplomacy towards Vanuatu: (1) the conduct of Indonesian public diplomacy has been dominated by state actor and less involve the role of non-state actors, (2) the three dimensions of Indonesian public diplomacy have not been optimazed, and (3) the existance of Melanesian Renaissance in Vanuatu domestic politics. Key words: Public Diplomacy, Indonesia, Vanuatu, United Liberation Movement for West Papua (ULMWP), Papua Separatist Movement.  Penelitian ini menjelaskan tentang diplomasi Indonesia kepada Vanuatu pada konteks upaya pemerintah Indonesia menyelesaikan masalah gerakan separatisme Papua. Analisis yang dilakukan pada tesis ini menggunakan teori diplomasi publik dari Leonard, Stead dan Smewing (2002). Hasil dari penelitian ini adalah gagalnya diplomasi publik Indonesia untuk mempengaruhi sikap politik Vanuatu atas isu Papua disebabkan karena belum optimalnya strategi diplomasi publik yang dijalankan Indonesia. Vanuatu tetap mendukung gerakan separatis Papua. Setidaknya ada tiga faktor yang menyebabkan lemahnya diplomasi publik Indonesia terhadap Vanuatu dalam isu Papua yaitu: (1) pelaksanaan diplomasi publik masih didominasi aktor negara dan kurang melibatkan aktor non-negara; (2) tidak optimalnya tiga dimensi diplomasi publik yang dijalankan Indonesia; dan (3) kuatnya pengaruh Melanesian Renaissance dalam perpolitikan domestik Vanuatu. Kata kunci: Diplomasi Publik, Indonesia, Vanuatu, United Liberation Movement for West Papua (ULMWP), gerakan separatisme Papua.